Letter from the Editor: Online Journal of Rural Nursing and Healthcare Readership Data - Jeri W Dunkin (Rural Nurse Organization; Binghamton University, 2007)
The Rural Nurse Organization has been very attentive to the needs of the Online Journal of Rural Nursing and Health Care. In 2005, software was installed that records information every time someone accesses the Journal. These recordings include time and date, specific pages accessed, and the location of the person accessing the Journal. As the editor, I am very excited to report that the Journal was accessed 528,780 times in 2006. One of the benefits to those whose articles are published in the Journal is the ability of RNO to report how many times in a given period readers have accessed a particular contributor's article. I have included a couple of pieces of information from the report for 2006. These reports are available each month on the website. Your RNO membership dues support this reporting function, as well as other information, including the digital library found on the web site. Please consider joining The Rural Nurse Organization if you haven't already, or renew your membership if you are currently a member. Go to http://www.rno.org/downloads/rno_membership_application.pdf to access the membership form. The form should be printed, filled out, and mailed to RNO. Thank you as always for your support of RNO and the Online Journal of Rural Nursing and Healthcare.